Translation Quality Assessment of Sitor Situmorang’s Translated Poetries by John McGlyn - Samuel Reynaldo Siboro, Umar Mono, Rudy Sofyan, Rusdi Noor Rosa, Rahmadsyah Rangkuti (Lembaga Bale Literasi, 2025)
This research is conducted to assess the quality of the Sitor Situmorang’s translated poetries by John McGlyn in Sastrawan Indonesia Book that published by Pusat Bahasa, Departemen Pendidikan Nasional on 2006. In this research used the translation quality assessment model proposed by Nababan et al. The TQA model by Nababan et al. focuses on three aspects, namely accuracy, acceptability, and readability. Three raters used in assessing the 11 Sitor Situmorang’s translated poetries by John McGlyn. The three raters are translator and have background in literature translation. Qualitative research is used in this research; in collecting data, this research used the observational method. Sudaryanto (1993) observational method is a method of collecting data by observing the use of the language and used distributional method in analyzing data. The final result of measuring these three aspects is the total value for the quality of the translation on a scale of 1-3. This research has the objectives to: 1) To find out the accuracy score of translated poetries by John McGlyn; 2) To find out the acceptability score of translated poetries by John McGlyn; 3) To find out the readability score of translated poetries by John McGlyn; 4) To find out the total score of translation quality of translated poetries by John McGlyn. Generally, the results indicated that the translation quality of the Sitor Situmorang’s translated poetries by John McGlyn, quite accurate, quite acceptable, and very readable. The score for the accuracy aspect is 2.6, for the acceptability aspect is 2.9, for the readability aspect is 3 and the total quality of the translation is 2.7.